RESIST Criteria: A biochemical algorithm to reduce the number of unnecessary upper endoscopies for the evaluation of portal hypertension in compensated HBV-cirrhotic patients. (March 2023) - Calvaruso, V.; Celsa, C.; Degasperi, E.; Di Maria, G.; Fichera, A.; Graceffa, P.; Rancatore, G.; Falco, G.; Di Martino, V.; Rizzo, G.E.M.; Grasso, M.; Bronte, F.; et al.
Abstract : Introduction: Non-invasive criteria to identify patients with compensated hepatitis B virus (HBV) cirrhosis who can avoid esophagogastroduodenoscopy(EGD) and predict the progression of low-risk esophageal varices(EV) are lacking. Aims: To evaluate the diagnostic performance of RESIST criteria: 1)to rule out high-risk EV(HRV) in viremic patients with compensated HBV cirrhosis at baseline; 2)to predict progression to HRV after viral suppression with nucleos(t)idic analogues(NUCs) in patients without HRV at baseline. Methods: All consecutive patients observed at 2 Italian referral centers with compensated viremic HBV cirrhosis who received NUCs therapy during follow-up were classified as RESIST low-risk if platelets were>120 × 10 9 /L and serum albumin>3.6 g/dL or RESIST high-risk if platelets were<120 × 10 9 /L or albumin<3.6 g/dL, before and after viral suppression. Outcomes were the presence of HRV at baseline and the progression to HRV during follow-up after viral suppression. Area under the receiver operating characteristic curve(AUROC) and decision curve analysis(DCA) were calculated for RESIST and compared with elastography-based criteria (Baveno VI, Expanded Baveno VI, and Baveno VII). Results: One-hundred-thirty-five Child-Pugh class A patients(mean age 50.8 years, 83.7% males) were included. At baseline, 35 patients(25.9%) had low-risk varices and 13(9.7%) had HRV. HRV were correctly classified in all 13 patients(100%) by Baveno VII and Baveno VI, in 12(92.3%) by RESIST and in 11(84.6%) by Expanded Baveno VI. Although RESIST missed 1 patient with HRV, they had the highest AUROC(0.73) and DCA demonstrates a higher net benefit compared to elastography-based criteria for ruling out HRV. After a median follow-up of 16.8 years, 9 out of 87(10.3%) patients without HRV at baseline developed HRV. RESIST showed higher specificity(85%) versus Baveno VII(59%) and VI(63%), avoiding a higher number(80%) of unnecessary endoscopies and showing the highest AUROC(0.90) and the highest net benefit in ruling out HRV compared to elastography-based scores. Discussion: RESIST criteria are useful to accurately predict HRV at baseline and the development of HRV after viral suppression by NUCs in patients with compensated HBV cirrhosis.